Determinants of Quality of Life among Post-COVID-19 Survivors in the Northeast of Thailand: A Cross-Sectional Analytical Study - Kanokporn Yodyot; Rajitra Nawawonganun; Wongsa Laohasiriwong; Kritsana Aunthakhot; Nopparat Senahad; Kittipong Sornlorm (National Journal of Community Medicine, 2026)
Background: The long-term impacts of Coronavirus Disease 2019 (COVID-19) may adversely affect survivors’ quality of life (QoL), particularly in low-resource settings. The objective was to identify factors associated with quality of life among COVID-19 survivors in the Northeast of Thailand. Methods: A cross-sectional study was conducted among 1,250 COVID-19 survivors selected using multistage sampling. Data were collected using structured questionnaires assessing sociodemographic characteristics, physical activity, COVID-19 prevention behavior, health literacy, COVID-19 knowledge, stress, healthcare and social support, and QoL measured by the WHOQOL-BREF-THAI. Generalized Linear Mixed Models (GLMM) with province-level random effects were used to identify factors associated with good QoL. Results: Overall, 34.56% of participants reported good QoL. Male gender (AOR = 1.64, 95% CI: 1.18-2.29), age